The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.4028/www.scientific.net/kem.291-292.67
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High Speed Grinding Using a CBN Wheel for a Mirror-Like Surface Finish

Abstract: There are strong demands for a machining process capable of reducing the surface roughness of sliding parts, such as auto parts and other components, with high efficiency. In this work, we attempted to grind hardened steel to a mirror-like surface finish with high efficiency using an ultra-high speed grinding process. In the present study, we examined the effects of the work speed and the grinding wheel grain size in an effort to optimize the grinding conditions for accomplishing mirror-like surface grinding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Similarly, diamond is the most popular material for abrasive machining of natural rock materials. Accordingly, many previous studies have focused on either the grinding of steels with CBN or the grinding of natural rock materials with diamond [1][2][3][4][5][6]. Some early studies reported the grinding of titanium alloy and steels with diamond [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, diamond is the most popular material for abrasive machining of natural rock materials. Accordingly, many previous studies have focused on either the grinding of steels with CBN or the grinding of natural rock materials with diamond [1][2][3][4][5][6]. Some early studies reported the grinding of titanium alloy and steels with diamond [7][8].…”
Section: Introductionmentioning
confidence: 99%